Os árabes nos antigos relatos portugueses do Índico - Farinha, António Dias (Finisterra, 2005)
Arabo- Islamic expansion quickly spread throughout Asia, Africa and Europe and in certain circumstances led to the conversion to Islam of many people that were generically labelled Moors. The arrival of the Portuguese in the East called for a more specific way in which to refer to the population coming from Arabia or that which underwent the process of Arabisation: Arabs, Alarves, Arabians, Bedouins, Maçaris and even names of tribes like Ben Jebra [Banû Djabr].